2017
DOI: 10.1080/19406940.2017.1359201
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting university sport policy in England: seeking a purpose in turbulent times?

Abstract: Given the fundamental change in political landscape of current higher education in England, it is timely to (re)consider the purpose of university sport and its fit with national sports policy. This research investigates the purpose of university sport; how university sport fits with national sport strategies, if at all; and whether universities and sport policy are capitalising on Higher Education (HE) sport. An interpretivistic public policy analysis was carried out using eight semi-structured interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The potential positive impact of PA levels upon perceived attainment may, in turn, result in improved graduate employment and longer-term employability. 21 Indeed, the present study found that the students who were more active were 27% more likely to report higher confidence that they would be employed upon graduation. Furthermore, across a range of employability skills, the students who were more active perceived themselves to be 12% to 58% better.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The potential positive impact of PA levels upon perceived attainment may, in turn, result in improved graduate employment and longer-term employability. 21 Indeed, the present study found that the students who were more active were 27% more likely to report higher confidence that they would be employed upon graduation. Furthermore, across a range of employability skills, the students who were more active perceived themselves to be 12% to 58% better.…”
Section: Discussionmentioning
confidence: 47%
“…For example, those who were members of a sports club were 53% more likely to rate themselves higher for teamwork. As mentioned, though data are sparse regarding the relationship between sport and attainment or employability, there is some evidence that sport may positively impact graduate employability, 21 and this would tend to support that perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Brunton (2017) found that only one out of the eight examined universities integrated sport into their university strategy with the explicit intention to achieve positive effects beyond physical fitness. They advocate for more research into the outcomes of sports on other parameters such as recruitment, retention, graduate employability, mental health, and student satisfaction.…”
Section: Focus Of This Studymentioning
confidence: 99%
“…Despite the potential for PA to be used as a vehicle for supporting these strategic goals there is an absence of data on the extent to which this is occurring in the university sector. The limited evidence in this area suggests that some universities have made efforts to support students' mental health by referring students who access on-campus counselling services to PA programs [90]. However, the uptake and efficacy of such initiatives is rarely assessed, and even less is known about whether PA is being used to support other strategic goals, such as academic success.…”
Section: Discussionmentioning
confidence: 99%